Evaluating the Efficacy of a Self-instructional Teaching Module on Home Care Management Knowledge for Renal Failure Patients Undergoing Hemodialysis in a Selected Hospital in Ambikapur, Chhattisgarh - Pudota Anthony Lourdu Mary (International Journal of Emergency and Trauma Nursing and Practices, 2023)
The kidneys, with their remarkable organization and precision in regulatory functions, exhibit a level of sophistication that can be likened to a divine quality. In a conducted study, a substantial correlation was identified between the pre-test knowledge scores of participants and specific demographic factors, particularly educational qualifications. The chi-square values calculated for educational qualifications were 18.85, and for previous knowledge, it was 6.56. In both instances, the calculated values surpassed the table values for chi-square at a significance level of p<0.05. Consequently, the research hypothesis was validated. Notably, age, sex, income, and occupation were determined to be insignificantly associated with pre-test knowledge scores.
Keywords: Self-instructional module; hemodialysis; home care management; renal failure